Qi: A Personal Take at the Intersection of TCM and the Natural Sciences - Mark Westmoquette (Society for Spirituality Studies, 2021)
In his paper, the author describes his own personal journey of discovering and understanding of subtle energy (Zh. Qi; Sa. prāna) as a way of furthering the virtual dialogue between natural sciences and spirituality. Using his own personal experiences from yoga and meditation as motivation, he discusses the way he has come to understand subtle energy in terms of the various scientific definitions and types of energy. In this regard, he considers the correspondence between subtle energy and the bioelectromagnetic field of the body, as well as how some physical effects could be understood if, under particular circumstances, this field came into body-wide coherence or resonance. Different types of energy are also explored as corresponding to the Qi of the meridian channels of Traditional Chinese Medicine. In conclusion, the author comes to such understanding of the notion of energy, which reaches the limits of language-based definitions, and this limit points at the potential of a more holistic understanding of energy and the nature of the Universe.